Sublethal concentrations of thiamethoxam induce transgenerational hormesis in cotton aphid, Aphis gossypii Glover - Hina Gul; Ali Güncan; Farman Ullah; Xinyuan Ning; Nicolas Desneux; Xiaoxia Liu (CABI Agriculture and Bioscience)
Abstract In agroecosystems, insects have to compete with chemical insecticides, which are frequently present at sublethal concentrations. The exposure of insects to these modest stresses is now well-established to generate hormesis effects, which has implications for controlling insect pests. In this study, we assessed the sublethal effects of thiamethoxam on the biological parameters of Aphis gossypii Glover (Hemiptera: Aphididae), adults (F0) and subsequent transgenerational impacts, i.e., on the progeny (F1 generation), using an age stage, two-sex life table analysis. Results showed that thiamethoxam exhibited high toxicity against adult A. gossypii with the LC50 of 0.313 mg L−1 after 48 h exposure. The LC5 and LC10 of thiamethoxam considerably reduced the adult cotton aphids (F0) longevity and fecundity, while the reproductive days were reduced only at LC10. The pre-adult stage was decreased, while the adult longevity, total longevity, and fecundity were significantly extended in F1 aphids after exposure of F0 aphids to the sublethal concentrations of thiamethoxam. Moreover, the key demographic parameters such as intrinsic rate of increase, finite rate of increase and reproductive days were significantly increased, while mean generation time and total prereproductive were significantly reduced in the progeny. No significant effects were observed on the net reproductive rate. Taken together, these results showed that the sublethal concentrations of thiamethoxam affect the directly exposed aphids (F0) while causing transgenerational hormetic effects on the F1 generation of A. gossypii. In conclusion, our research showed that thiamethoxam has both sublethal and transgenerational effects on cotton aphids; it could be effective in IPM programs targeting this key pest.